PERMASALAHAN SOSIAL DALAM NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY - lilis sari; Maulfi Syaiful Rizal (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
Literary works are the result of imitating or depicting the reality of phenomena that occur in human real life because literary works themselves are a reflection of society. Therefore, literature is an expression of human life that cannot be separated from the problems that exist in society. One of the literary works that express the reality of social life is a novel, one of which is a novel entitled Ayat-Ayat Cinta. This study aims to examine the description of social problems in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy and find out the driving factors of these social problems. The method used is a descriptive qualitative approach to the sociology of literature. Data was collected using the technique of observing and noting using the observation method. The findings obtained in this study indicate that there are descriptions of social problems in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy, in the form of discrimination, domestic violence, family disorganization, school bullying, prostitution, polygamy in the western paradigm, and poverty. The various social problems found indicate that factors are driving these social problems in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy, such as psychological factors and cultural factors